Theoretical and Methodological Approaches to E-Learning Implementation in Higher Schools - Borova, T. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the ground of the conception of sustainability society development, basic approaches (synergistic, activity, competence, communicative, information and communications technology) and objective laws of e-learning in a higher educational establishment. The methods of synthesis, actualization and systematization of foreign and native literature are used on the questions of modern education development with e-learning application at higher school, paying attention to the processes of globalization. The modern stage of development of information society is analysed, where the basis are education and knowledge. The results of analysis of the basic universally recognized didactics principles of studies are reflected within the limits of electronic studies. The results of analysis of the basic universal recognized didactics principles of learning are reflected within the framework of e-learning. The advantages and disadvantages of e-learning are distinguished in educational activity of higher educational establishments. The priorities of blended learning are outlined on the modern stage of higher education development. The system of influence of electronic devices on an educational process is shown. The forms of communication, that are widespread in e-learning, are considered, taking into consideration changing the role of an educational manager as a leader, a teacher as facilitator and a student as an active participant of the learning process. It is analysed necessary skills that are required to develop learning e-materials. A research result is a ground of necessary approaches and conditions for effective application of e-learning in higher educational establishments, which will give an opportunity to improve the quality of specialists of new generation preparation.